Safety and efficacy of rotational atherectomy for the treatment of undilatable underexpanded stents implanted in calcific lesions. Issue 2 (10th November 2016) - Ferri, Luca A.; Jabbour, Richard J.; Giannini, Francesco; Benincasa, Susanna; Ancona, Marco; Regazzoli, Damiano; Mangieri, Antonio; Montorfano, Matteo; Colombo, Antonio; Latib, Azeem
Abstract : Objectives: Coronary stent underexpansion is a known risk factor for in‐stent restenosis and stent thrombosis. There are limited options once noncompliant balloons have failed to achieve optimal stent expansion. Excimer Laser Coronary Angioplasty with contrast medium injection is one possibility, but not readily available. Rotational atherectomy is an alternative, and has been described in case reports, but concerns exist regarding safety. Methods: All consecutive patients undergoing rotational atherectomy for symptomatic in‐stent restenosis due to stent underexpansion resistant to noncompliant balloon postdilatation between January 2005 and December 2015 were analysed. Results: A total of 16 patients underwent treatment during the study period and the procedure was successful in 14 cases (87.5%). The mean postprocedural minimal lumen diameter increased by 2.3 ± 0.8 mm and percentage diameter stenosis decreased from 82.17% ± 17.2% to 11.9% ± 9.1%. Intraprocedural complications occurred in two patients (burr entrapment successfully managed percutaneously and periprocedural myocardial infarction). At 1‐year follow‐up, the incidence of target lesion revascularisation was 13.3% (2 out of 15 patients), and one patient died from noncardiac death. Conclusion: In this small series of underexpanded stents, rotational atherectomy was an effective treatment for resistant stent underexpansion with acceptable outcomes. © 2016 Wiley Periodicals, Inc.